PENGARUH TEKANAN EKSTERNAL, KETIDAKPASTIAN LINGKUNGAN, KOMITMEN MANAJEMEN DAN SISTEM PENGENDALIAN INTERN PEMERINTAH TERHADAP PENERAPAN TRANSPARANSI PELAPORAN KEUANGAN (Studi Empiris Pada Organisasi Perangkat Daerah Kota Dumai) - Ratih Anggraini; Zulbahridar Zulbahridar; Al Azhar L (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study examines the effects of external pressures, environmental uncertaintly, management commitments and the government intern control systems on thetransparency of financial reporting.The population in this research is the organization of dumai city area of 34 opd. Of the existing population then obtained samples in this study as many as 102 respondents. Sampling technique using purposive sampling method, while the data processing method used by SPSS version 20.0 as software to process data. The results of the research indicate that external pressure has significant effect on thetransparency of financial reporting. Environmental uncertainly has a significant effect on thetransparency of financial reporting. Management commitment has a significant effect on thetransparency of financial reporting. And the government's internl control system have a significant effect on thetransparency of financial reporting.Keywords : External Pressure, Environmental Uncertainly, Management Commitmen, the government’s intern control system and transparency of financial reporting.